2009
DOI: 10.1002/humu.21003
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sequence variants in the human mitochondrial genome using high-resolution melt (HRM) profiling

Abstract: Identifying mitochondrial DNA (mtDNA) sequence variants in human diseases is complicated. Many pathological mutations are heteroplasmic, with the mutant allele represented at highly variable percentages. Highresolution melt (HRM or HRMA) profiling was applied to comprehensive assessment of the mitochondrial genome and targeted assessment of recognized pathological mutations. The assay panel providing comprehensive coverage of the mitochondrial genome utilizes 36 overlapping fragments (301-658 bp) that employ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…For instance, the m.4456C→T variant (Figure 2a) has also been reported as a polymorphic change in MITOMAP. 35 This variant was identified within one of the 36 short PCR amplicons tiled to cover the entire mtDNA. Close examination revealed that the mtDNA primers used for the amplification of the fragment encompassing the m.4456C→T variant were completely homologous to a NUMT sequence on chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the m.4456C→T variant (Figure 2a) has also been reported as a polymorphic change in MITOMAP. 35 This variant was identified within one of the 36 short PCR amplicons tiled to cover the entire mtDNA. Close examination revealed that the mtDNA primers used for the amplification of the fragment encompassing the m.4456C→T variant were completely homologous to a NUMT sequence on chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…Rouleau et al [2009] used the possibility provided by some instruments to perform quantitative PCR and HRMA in one instrument to scan for both quantitative (deletions/duplications) and qualitative nucleotide changes in one assay. Finally, Dobrowolski et al [2009] described the use of HRMA to scan the entire 16.6 kb human mitochondrial genome (mtDNA) for sequence variants in less then 2 hr. Identification of mtDNA variants is complicated, as many are heteroplasmic, with the variant allele present at highly variable percentages.…”
Section: Applications Mutation Detectionmentioning
confidence: 99%
“…In fact, based on these figures, HRMA prescreening of a five-exon gene is already cost-effective. In addition, to detect somatic changes or heteroplasmy [Dobrowolski et al, 2009], HRMA seems more sensitive then sequencing (see Quantification).…”
Section: Pressequence Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time PCR coupled with high-resolution melt (HRM) analysis fulfills these criteria (23,(28)(29)(30)(31)(32)(33)(34).…”
Section: Schreeg Et Almentioning
confidence: 99%